Diferença mínima clinicamente importante do Bronchiectasis Health Questionnaire (BHQ) na exacerbação pulmonar aguda e sua recuperação em pacientes com bronquiectasia - Luppo, Adriano (2021)
Introduction: The Bronchiectasis Health Questionnaire (BHQ) is a specific questionnaire that assesses the quality of life of patients with bronchiectasis. However, the minimal clinically important difference (MCID) was not presented. Objective: To determine the DMCI of the BHQ, during and after recovery from a pulmonary exacerbation in patients with bronchiectasis. Secondarily, investigate MCID by sex and by bronchiectasis severity. Methods: Observational, prospective study. Participants were encrypted using spirometry, an incremental shuttle walk test (ISWT), and the severity of bronchiectasis was assessed using the Bronchiectasis Severity Index (BSI) and E-FACED. At the routine outpatient visit, if clinically stable, participants completed the BHQ and a modified Medical Research Council dyspnea scale (mMRC). For a period of 36 months, they were monitored (monthly) by telephone contact to assess clinical stability. In case of pulmonary exacerbation, participants responded once more to the BHQ (exacerbation) and again 14 days after the end of antibiotic therapy (recovery). Results: Of 85 patients, 60 patients (21 men, 48.0 ± 12 years, FEV1 54 ± 18% predicted, E-FACED: median 3 [interquartile range: 1-7]) similar at least one episode of exacerbation. There was variation in BHQ scores from baseline (mean 58.0 ± 7.83 points) for exacerbation (mean 49.0 ± 8.7; points) and from baseline (mean 59.0 ± 8.85 points) points). The minimum clinically important difference changes in BHQ during pulmonary exacerbation and recovery, respectively, are between -3.65 and 3.53 points. There was no statistical difference in the BHQ scores at the time of exacerbation and recovery, when the groups were divided between gender and bronchiectasis severity using E-FACED and BSI scores, therefore, the CIDM for gender and severity was not strengthened. Conclusion: The MCID was chosen for the BHQ, which proved to be a responsive instrument to changes in quality of life, through the presence of an acute pulmonary exacerbation and its recovery.